2018
DOI: 10.1021/acscatal.8b01925
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Multifunctional Organocatalysts for Ambient Conversion of Carbon Dioxide into Cyclic Carbonates

Abstract: A series of pincer-type compounds possessing an N-heterocyclic carbene precursor and a carboxyl group as proton transfer agent were synthesized and used as organocatalysts for the cycloaddition of epoxides with CO 2 . In this context, we have demonstrated the high activity of these one-component organocatalysts in the CO 2 transformation to cyclic carbonates under ambient conditions (room temperature, 1 bar of CO 2 ). The catalytic potential of these multifunctional organocatalysts on challenging internal epox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
100
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(103 citation statements)
references
References 113 publications
3
100
0
Order By: Relevance
“…However, styrene oxide, as well as other epoxides giving stable carbocations, often gave partial racemization, which is accounted for a partial Sn1 mechanism. It should be noted that the scorpionate catalyst (entry 43) was rationally designed by authors on the basis of the mechanism and combining experimental and computational efforts [84].…”
Section: Cyclic Carbonatesmentioning
confidence: 99%
“…However, styrene oxide, as well as other epoxides giving stable carbocations, often gave partial racemization, which is accounted for a partial Sn1 mechanism. It should be noted that the scorpionate catalyst (entry 43) was rationally designed by authors on the basis of the mechanism and combining experimental and computational efforts [84].…”
Section: Cyclic Carbonatesmentioning
confidence: 99%
“…ILs and their derivatives have favorable CO 2 ‐philic natures, and their anions are the active nucleophiles for the ring opening of epoxides, normally the rate‐determining step in the CO 2 cycloaddition . As a result, a great number of IL‐derived materials have been established as adsorbents and catalysts for CO 2 capture and fixation .…”
Section: Introductionmentioning
confidence: 99%
“…3). 46 The results indicated that the catalyst 19e containing phenolic hydroxyl group was catalytically more active than other catalysts. Thus, in the presence of 4 mol% of organocatalyst 19e under ambient conditions a range of substituted epoxides 20 underwent coupling with CO 2 provided the corresponding carbonates 21 in good to excellent yields (Scheme 12).…”
Section: Ionic Liquid Catalyzed Reactionsmentioning
confidence: 94%